Confronting the Challenges of Graduate Education in Sub-Saharan Africa - Hayward, Fred M.; Ncayiyana, Daniel J. (International Higher Education, 2015)
This piece focuses on the current state of graduate education in Sub-Saharan Africa spelling out some of the challenges faced as well as areas of improvement over the last five years. We emphasize the critical importance of graduate education to national development. We make suggestions about creating high quality graduate programs including the critical need for more PhD faculty members and expanded quality research at Africa’s best universities.